Anaphylaxis during general anesthesia: A case report and literature review - Singkam, Krittiyaporn; Lao-araya, Mongkol (Biomedical Sciences and Clinical Medicine, 2018)
An anaphylaxis during general anesthesia does not occur very frequent, but associates with significant mortality. The causes of anaphylaxis can be complex because of the large number of medications administered in the same time. All patients with history of perioperative anaphylaxis should have an extensively appropriate evaluation. The allergist is responsible for identifying the cause and other agents likely to be safe for future use. Here, we reported a patient with severe allergic reactions twice due to neuromuscular blocking agents; atracurium and cisatracurium, which were confirmed by allergy skin test. Furthermore, we reviewed the literatures concerning the diagnosis and prevention of patients with anaphylaxis in the perioperative setting.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">